2021
DOI: 10.1371/journal.pntd.0009593
|View full text |Cite
|
Sign up to set email alerts
|

Integrated human-animal sero-surveillance of Brucellosis in the pastoral Afar and Somali regions of Ethiopia

Abstract: Background Brucellosis is widespread in Ethiopia with variable reported prevalence depending on the geographical area, husbandry practices and animal species. However, there is limited information on the disease prevalence amongst pastoral communities, whose life is intricately linked with their livestock. Methodology We conducted an integrated human-animal brucellosis sero-surveillance study in two adjacent pastoral regions, Afar and Somali region (SRS). This cross-sectional study included 13 woredas (distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…In the previous study, the prevalence in the pastoralist community was (3•0%) and 4•5% in veterinary personnel [12]. Moreover, prevalence of the current study was very low compared to the results reported in a similar study conducted in Afar (48.3%) and in Somali (34.9%) regions, Ethiopia which has similar environmental setting and husbandry system to it [16]. In South Sudan the seroprevalence was 27.2 % as reported by the authors [18].…”
Section: Discussioncontrasting
confidence: 67%
“…In the previous study, the prevalence in the pastoralist community was (3•0%) and 4•5% in veterinary personnel [12]. Moreover, prevalence of the current study was very low compared to the results reported in a similar study conducted in Afar (48.3%) and in Somali (34.9%) regions, Ethiopia which has similar environmental setting and husbandry system to it [16]. In South Sudan the seroprevalence was 27.2 % as reported by the authors [18].…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, the government has launched the National Brucellosis Technical Working Group (NBTWG) to spearhead collaborative efforts among government and private sectors, partners and universities, to coordinate and synergistically implement prevention and control efforts through the One Health approach [3]. Although the disease has widespread characteristics in humans and their livestock, particularly in occupational and pastoral communities, limited information is available regarding its prevalence, transmission and risk factors among communities [45].…”
Section: Status Of Bovine and Human Brucellosis In Ethiopiamentioning
confidence: 99%
“…Accordingly, a very recent study in Afar, "Integrated human-animal sero-surveillance of brucellosis in the pastoral Afar and Somali regions of Ethiopia," has reported an overall cattle brucellosis seroprevalence of 7.2% and 6.2% in Afar and Somali, respectively% [45] In the same year, Getahun reported an 0.6% prevalence in dairy cows with recent abortion history [47]. Another cross-sectional study in the Jimma Zone, Oromia Region, has reported an animal and herd level cattle prevalence of 16.4% and 4.3%, respectively [64].…”
Section: Seroprevalence Of Bovine Brucellosismentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, brucellosis can cause adverse events during pregnancies and, if left untreated, may result in long-term cardiac, neurological or immunological complications [ 8 ]. Brucellosis is also considered endemic in Ethiopia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%